PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Muhammad Anas Fadli (ADMINISTRASI PUBLIK, 2021)
Muhammad Anas Fadli. the influence of organizational culture on employee performance (case study of PT. JASAMARGA toll road operator Balikpapan-Samarinda section).In this study, the type of research taken is descriptive quantitative research that aims to provide a systematic, factual and accurate description in explaining the existing phenomena, while the quantitative approach is a research that demands the use of numbers, starting from data collection, interpretation of the data, and appearance of the result.Based on the results of hypothesis testing, it can be seen that there is a positive and significant influence between organizational culture on employee performance at PT. JASAMARGA toll road operator for the Balikpapan-Samarinda segment. This can be seen from the significance value of the probability which is smaller than 0.05, which is 0.000 and the regression coefficient is 0.782 with a positive sign. With a vulnerable correlation of 0.80 - 0.100 so it can be concluded that between organizational culture and employee performance of PT. JASAMARGA toll road operator Balikpapan-Samarinda segment has a very strong level of relationship. Thus, the hypothesis which states that organizational culture has a positive and significant effect on employee performance can be accepted.